Scientific Opinion on the state of the science on pesticide risk assessment for amphibians and reptiles. (23rd February 2018) - ,; Ockleford, Colin; Adriaanse, Paulien; Berny, Philippe; Brock, Theodorus; Duquesne, Sabine; Grilli, Sandro; Hernandez‐Jerez, Antonio F; Bennekou, Susanne Hougaard; Klein, Michael; Kuhl, Thomas; Laskowski, Ryszard; et al.
Abstract: Following a request from EFSA, the Panel on Plant Protection Products and their Residues developed an opinion on the science to support the potential development of a risk assessment scheme of plant protection products for amphibians and reptiles. The coverage of the risk to amphibians and reptiles by current risk assessments for other vertebrate groups was investigated. Available test methods and exposure models were reviewed with regard to their applicability to amphibians and reptiles. Proposals were made for specific protection goals aiming to protect important ecosystem services and taking into consideration the regulatory framework and existing protection goals for other vertebrates. Uncertainties, knowledge gaps and research needs were highlighted. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1357/full